The crystal structure of [bis(2,2′-bipyridine-6-carboxylato-κ3N,N,O)magnesium(II)]dihydrate, C22H18N4O6Mg - Xi-Shi Tai; Hong-Chang Li (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C22H18N4O6Mg, orthorhombic, Pbca (no. 61), a = 15.3055(2) Å, b = 15.1214(2) Å, c = 18.1048(2) Å, V = 4190.19(9) Å3, Z = 8, Rgt(F) = 0.0376, wRref(F2) = 0.1069, T = 296 K.